Селянський повстанський рух Півдня України в контексті Української революції 1917—1921 рр. - Капустян, Г. (Український визвольний рух, 2011)
У статті йдеться про селянський повстанський рух на Півдні України, зокрема махновщину в контексті Української революції 1917—1921 рр. як частину селянської революції 1902—1922 рр. Порівняно форми і методи боротьби Українських січових стрільців і революційної повстанської армії Махна. The article covers peasant insurgency movement in the South of Ukraine, including the term of Makhnovshchyna, in the context of the Ukrainian Revolution in 1917—1921 as a part of the Peasant revolution of 1902—1922. An attempt to compare the forms and methods used by the Ukrainian Sich Riflemen (Sitchovi Striltsi) formation and the Revolutionary Insurrectionary Army of Ukraine under Makhno leading has been made.